Apigenin Induces Apoptosis and Inhibits Migration in Human Cholangiocarcinoma Cells - Mayurachat Kaewmanee; Temduang Limpaiboon; Nipaporn Ngernyuang (Toxics)
Cholangiocarcinoma (CCA) is a rare and highly aggressive cancer of the biliary tract, associated with poor clinical outcomes due to late diagnosis, extensive metastasis, drug resistance, and limited treatment options. Apigenin, a natural flavonoid, has been found to exhibit anticancer properties in several types of human cancer cells. Therefore, apigenin may be relevant to developing chemotherapeutic agents for cancer treatment. In this study, we examined the effects of apigenin on cell viability, cell cycle distribution, apoptosis, and cell migration in human CCA cell lines (KKU-M055) under in vitro conditions. The results demonstrate that apigenin significantly suppressed specific CCA cell proliferation by inducing cell cycle arrest at the G2/M phase and promoting cell apoptosis in KKU-M055 cells while exhibiting low toxicity in immortalized MMNK1 cells. Apigenin enhanced apoptotic features, including nuclear fragmentation and the loss of mitochondrial membrane potential. Furthermore, apigenin induced the apoptosis of KKU-M055 cells in both extrinsic and intrinsic pathways by activating caspase-8, -9, and -3/7. Moreover, apigenin inhibited KKU-M055 migration. Our study suggests apigenin as a promising candidate for treating CCA, and these findings provide theoretical support for the further development and potential application of apigenin in clinical CCA therapy.